Vitamin A Levels Among Pre-School Children of Central and Western China - Chen, Qian; Liu, Yongfang; Chen, Li; Chen, Jie; Yang, Ting; Cheng, Qian; Li, Tingyu (Frontiers in Public Health, 2021)
Objective: To investigate vitamin A deficiency of pre-school children in central and western China for developing strategies to prevent and control vitamin A deficiency (VAD) among children. Design: From November 2018 to September 2019, a total of 2,194 healthy children aged 2–6 years were enrolled. Serum retinol levels in the children were detected by liquid-phase tandem mass spectrometry. In addition, social demographic and dietary questionnaires were collected through interviews with children's caregivers. Setting: The participants were enrolled in 12 cities or their subordinate jurisdictions in the central and western regions of China. Participants: Two thousand one hundred and ninety four healthy children aged 2–6 years old. Results: Overall, 35.51% (779/2,194) of the children were found to be vitamin A insufficient (VAI, serum retinol < 1.05 μmol/L). Elder children had a higher risk to suffer from VAI, with proportions of 25.00% (87/348), 28.92% (142/491), 38.38% (256/667), and 42.73% (294/688) among children aged 2, 3, 4, and 5 years, respectively. Vitamin A levels were also positively correlated with per capita income (AOR = 1.18) and regional economic level (0.71), and the frequency of milk intake (0.91). Conclusions: The incidence of VAI was higher among children aged 2–6 years, and the incidence of VAI increases with age. VA levels were positively correlated with levels of economic development in the family and region. So prevention strategies for VAD need to focus on pre-school children, especially dairy intake and developing regions.